The ILO @ 100: Addressing the Past and Future of Work and Social Protection - Christophe Gironde; Gilles Carbonnier (Brill Nijhoff, 2019)
On the occasion of the centenary of the International Labour Organization (ILO), this 11th special issue of International Development Policy explores the Organization's capacity for action, its effectiveness and its ability to adapt and innovate. The collection of thirteen articles, written by authors from around the world, covers three broad areas: the ILO's historic context and contemporary challenges; approaches and results in relation to labour and social protection; and the changes shaping the future of work. The articles highlight the progress and gaps to date, as well as the context and constraints faced by the ILO in its efforts to respond to the new dilemmas and challenges of the fourth industrial revolution, with regard to labour and social protection.
Keywords: 320; Arbeitswelt; Arbeitnehmerschutz; Sozialstandards; Digitalisierung; Strukturwandel; Welt